Internal Factors Influence on Project Management Maturity Assessment - Ahmed, Muhammad S (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2018)
The study acts as a pilot research to investigate the influence of organizations internal dynamics on PMM assessment levels and to outline a methodology that can help us to quantify it. It aims to analyze the influence of organizations internal dynamics on project management maturity, (PMM), assessments and how they can change the assessment results. Specifically, it addresses the impact of internal organizational influences, like organization culture, leadership & leadership hierarchy, and emotional stability on the assessments of organization project management maturity. The methodological research approach for this study was a survey of 129 professionals. These professionals represent both manufacturing and service sectors industries that utilize project management extensively. Data were analyzed using multiple regression models with SPSS data processing results show that organization’s internal factors significantly influence project management maturity assessments. The internal forces like organization culture and leadership/ leadership hierarchy significantly increase the PMM levels while emotional stability greatly reduces the PMM levels. These results can help upper management to better understand the PMM assessment results while academics can use it to amend maturity models and for conducting a more extensive longitudinal research.